Kaiser Haq: - Sheikh Mehedi Hasan (Crossings, 2009)
Like most of the noteworthy South Asian poets writing in English. Kaiser Haq has moved away from traditional verse from and stereotypical themes. He has been articulating his cultural identity uniquely in the context of Bangladesh—a third world country afflicted with poverty, hunger, floods, tornados, political turmoil and recently corruption—with a treasure house of distinctive poetic images tinged with a sense of irony and humour. This paper explores various aspects of Kaiser Haq’s poetry with special emphasis on the poems dealing with cultural duality inherited from the colonial presence in the Indian subcontinent. In some of the poems, Haq deliberately uses colonial Babu English-inflected and distinctive idioms, non-stop use of the continuous tense and expressions shaped and affected by the first language of a colonial subject only to ‘mock’ the colonial legacy that we more or less still bear. Besides, his ironic stand while critiquing the colonial burden in his society affirms his existence as a postcolonial poet. Another notable aspect of Haq’s poetry is how he clings to his oi.vn cultural reality by refusing to join the immigration queue and become a Diaspora writer. The paper also focuses on his ironic portrayal of the political system existing in the postcolonial Bangladesh. In fact, the paper tries to discover how poetry can bear witness-instead of creating ego-centred lyrical vivacity-to a social system where language, politics, culture and custom are reshaped or reconstructed by different aspects of postcoloniality.